The impact of tax planning, profitability, liquidity and sales growth on firm value in the company infrastructure sector 2018-2022 - Nur Saila; Heni Agustina (Enrichment : Journal of Management, 2023)
The background of this research is the decline in share prices of several infrastructure companies in the fourth quarter of 2022 before the end of the PPKM implementation period. In this study there are several factors that can affect the firm value, namely tax planning, profitability, liquidity and sales growth. The purpose of this study is to determine the impact of Tax Planning, Profitability, Liquidity and Sales Growth on Firm Value. The population in this study are infrastructure sector companies that are included in the infrastructure sector stock index (IDXINFRA) group listed on the Indonesia Stock Exchange (IDX) in 2018-2022. The sampling method used was purposive sampling method and obtained 15 companies with a total sample of 75 financial statements which were the object of research. The data analysis method is in the form of quantitative analysis using multiple linear regression analysis and hypothesis testing using the SPSS 26 program. The results show that tax planning has a negative and significant effect on firm value, profitability has a positive and significant effect on firm value, liquidity and sales growth have no effect on firm value. The benefits of this research is for future researchers, it can be used as a comparison with the results of previous studies. For academics it can be used to dig deeper in order to strengthen existing theories, both for teaching materials and for further research. The company is expected to be used as a reference for managers in making effective and efficient business decisions. Investors can use the results of this research as a basis for making decisions before investing.